Struktur Kepemilikan Dan Karakteristik Perusahaan Terhadap Agresivitas Pajak Perusahaan Manufaktur Di Indonesia - Choirul Anwar Pratama, Nova; Nurlaela, Siti; Hendra Titisari, Kartika (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
The government and taxpayers have different interests, thus raising the tendency of taxpayers to minimize the tax paid. This research purpose to determine and analyze the impact of ownership structure (managerial ownership and institutional ownership) and firm characteristics (liquidity, gender diversity on board) on tax aggressiveness. For this research 134 manufacturing firms listed on Indonesia Stock Exchange in the 2013-2018 period used as population. By using purposive sampling selected 12 firms that used to be sample. Analytical method used is panel data regression and model selected Random Effect in Eviews 9. Research findings that liquidity affects tax aggressiveness, while other variable managerial ownership, institutional ownership, and gender diversity on the board do not have an impact on tax aggressiveness.